2015
DOI: 10.1007/s11136-015-1177-2
|View full text |Cite
|
Sign up to set email alerts
|

Developing a measure of medication-related quality of life for people with polypharmacy

Abstract: The study presents a psychometric evaluation of a measure used to assess MRQoL of patients with polypharmacy. The instrument is practical to administer in clinics and provides a valuable adjunct to the outcome measurement for patients with polypharmacy. Further research on the sensitivity of this instrument to medication change in multi-medicated patients is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…In the present study, we used the Medication-Related Quality of Life Scale version 1.0 (MRQoLS-v1.0) questionnaire, which is specific to patients with medication problems and has been recently validated as a measure of medication-related QoL (MRQoL) in patients with polypharmacy[15]. A better understanding of these medications related factors in older patients with polypharmacy may be useful to tailor interventions to the needs of individual patients in efforts to improve overall care and HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we used the Medication-Related Quality of Life Scale version 1.0 (MRQoLS-v1.0) questionnaire, which is specific to patients with medication problems and has been recently validated as a measure of medication-related QoL (MRQoL) in patients with polypharmacy[15]. A better understanding of these medications related factors in older patients with polypharmacy may be useful to tailor interventions to the needs of individual patients in efforts to improve overall care and HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…A further instrument, developed in Taiwan and published since the literature review was completed, claims to measure Medication-Related Quality of Life, 76 a term originally adopted for the LMQ. 77 This instrument was developed based on subjective well-being scales plus patient interviews and consists of 14 items, covering only three domains: role limitations, self-control, and vitality.…”
Section: Discussionmentioning
confidence: 99%
“…77 This instrument was developed based on subjective well-being scales plus patient interviews and consists of 14 items, covering only three domains: role limitations, self-control, and vitality. 76 Only the first of these relates directly to medicines burden, as discussed in this review; therefore, this instrument too is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Keijsers and others showed that the walking speed of a healthy subject on a force plate can be predicted by the subject's plantar pressure center, and the average pressure center speed predicts that the healthy subject will be 95% of his preferred walking speed [51]. Accuracy, precision can reach 0.2m / s. Although weightbearing magnetic resonance diagnosis has the characteristics of directly displaying lesions, its value as a conventional diagnostic tool has been questioned because of its traumatic nature [52].…”
Section: Introductionmentioning
confidence: 99%